Reliability Analysis of Covid-19 Risk Management System in Malaysia Higher Learning Institution - Khairil Anuar, Abdul Hamid; Ezrin Hani, Sukadarin; Widia, Mirta (IEOM Society, 2022)
Reliability concerns the extent to which a measurement of a phenomenon provides a stable and consistent result. Reliability is also concerned with repeatability. For example, a test will be reliable if measurement is repeated and conducted under constant conditions, hence will give the same result. This article attempts to present the result of a reliability study in the development of the Covid-19 risk management system in a Malaysia Institution of Higher Learning. The system is called C19-HIRAO. Two types of reliability study were explored for this purpose namely interrater reliability study and test-retest method. Interrater reliability study consists of Cohen’s Kappa statistic and percent agreement (conventional method). Interrater Cohen’s Kappa and Test-retest method were performed by the raters from Universiti Malaysia Pahang (UMP). The result proved that the developed C19-HIRAO has achieved an almost perfect agreement (0.92), moderate agreement (0.75), and very high relationship (1.00) for Interrater percentage agreement, Interrater Cohen’s Kappa, and test-retest method respectively. In conclusion, although this system is still newly developed, the risk rating value obtained is consistent among different raters. The value of this risk rating is also stable and reliable over the time when test-retest reliability is conducted within the stipulated time frame by the same rater.